PENGARUH PERTUMBUHAN ASSET DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PADA PERUSAHAAN RETAIL YANG TERDAFTAR DI BURSA EFEK INDONESIA - Hayatul Fuad; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of asset growth and sales growth on profitability. This study uses a descriptive quantitative approach which is analyzed using statistical-based partial and multiple regression analysis. The population of the study are retail companies listed on the Indonesia Stock Exchange in 2015 – 2019 as many as 8 companies. The results of this study are asset growth has a positive and significant effect on profitability and sales growth has a significant effect on profitability. The analytical technique used is multiple linear regression analysis with F test and t test. Based on the results of the F test, it is known that the significance value is less than 0.05, which is 0.000, this indicates that the independent variables of asset growth and sales growth simultaneously have a significant effect on profitability. Based on the results of the T test, there is a significant effect of the sales growth variable (X2) on profitability (Y), which is 4.183. Where tcount = 4.183 > t table = 1.943 and sig 0.00 Ftable 5.67 and sig o, oo